Effects of different level of watermeal in feed on growth performances of tinfoil barb (Barbonymus schwanenfeldii) - หมั่นกิจ จิตติมา (Journal of Vocational Education in Agriculture, 2019)
The objectives of this research were to find an appropriate feed formula on growth of tinfoil barb (Barbonymus schwanenfeldii) and to find the cost of the fish feed. The experimental design was Completely Randomized Design (CRD). There were 4 treatments (feed formula) and 3 replications, treatment 1 used commercial feed and treatment 2-4 used local-made feed mixed with 0 10 and 20% watermeal, respectively. The duration of the experiment was 12 weeks. After the experiment, the average weight gained of fish, average daily gain (ADG), feed conversion ratio (FCR) and survival rates of all treatments were not significant different (P>0.05). The costs of all fish feeds were not significant different (P>0.05) but the cost of feed mixed with 10% watermeal was the lowest to produce 1 kg fish. It was recommended that 10% watermeal mixed in fish feed was the appropriate feed to reduce the cost of fish culture investment.